Analisis Pengaruh Motivasi Kerja dan Pelatihan Kerja Terhadap Produktivitas Karyawan PT Global Insight Utama Green Nitrogen - Genta Raihan; Rakhmat; Surtini (Mulia Pratama, 2024)
This author aims to explain whether work motivation and work training variables have a significant effect on employee productivity at PT Global Insight Utama Green Nitrogen. This type of research uses data collection methods (observation), interviews and uses a list of questions (questionnaire). The sample method used was a saturated sampling technique, namely 32 respondents. Data analysis was carried out using multiple linear regression analysis methods, Determination coefficient analysis, t test, f test in the SPSS Version 22 program. The results of this research show that partially work motivation and work training have a strong and positive effect on employee productivity seen from the results of the multiple regression coefficient analysis Y`=12.305 + 0.175(X1) +0.536 (X2) meaning that work motivation and work training (X1 and X2 = 0) then employee productivity is 12.305 and if work motivation and work training are (X1 and X 2= 1) the performance is 0,175 and 0,53 for X2. Based on the SPSS program R2 determination coefficient analysis calculation, it is 0.669. The correlation analysis of R2 determination is obtained with a value of Kd = (0.669 x 0.6669=0,0,448) 48% and the remaining 100% -44% = 55,2% incfluenced by other variables. Based on the results of the partial work motivation test, tcount is 0.968<2.010 ttable with a significance value of 0.00 because the probability of significance is much smaller than 0.05, then H0 is accepted, and Ha is rejected. This shows that partially, work motivation does not have a positive and significant influence on job training. Based on the partial test of the job training variable, it is stated that the t count is 3.241>2.010 ttable, with a significance value of 0.05, then H0 is rejected and Ha is accepted. This shows that job training has a positive and significant influence on employee productivity. Based on the hypothesis test, f obtained a value of 19.065 with df numerator 2 and df denominator 48, you will get ftable of 3.19 because fcount 19.065>ftable>3.19, then H0 is rejected and Ha is accepted, meaning there is a significant influence between work motivation (X1) and job training (X2) influence the employee productivity variable (Y) at PT Global Insight Utama Green Nitrogen.